Optically controlled electroresistance and electrically controlled photovoltage in ferroelectric tunnel junctions - Jin Hu, Wei (Nat Commun, 2016)
Ferroelectric tunnel junctions (FTJs) have recently attracted considerable interest as a promising candidate for applications in the next-generation non-volatile memory technology. In this work, using an ultrathin (3 nm) ferroelectric Sm(0.1)Bi(0.9)FeO(3) layer as the tunnelling barrier and a semiconducting Nb-doped SrTiO(3) single crystal as the bottom electrode, we achieve a tunnelling electroresistance as large as 10(5). Furthermore, the FTJ memory states could be modulated by light illumination, which is accompanied by a hysteretic photovoltaic effect. These complimentary effects are attributed to the bias- and light-induced modulation of the tunnel barrier, both in height and width, at the semiconductor/ferroelectric interface. Overall, the highly tunable tunnelling electroresistance and the correlated photovoltaic functionalities provide a new route for producing and non-destructively sensing multiple non-volatile electronic states in such FTJs.